Teoria Histórico Cultural e Literatura Infantil: possibilidades para potencializar o desenvolvimento de capacidades humanas das crianças da/na Educação Infantil. - Oliveira, Gleice Kelly Pantoja de (Brasil, 2022)
This Course Completion Paper (TCC) aimed to investigate the possible contributions possible contributions of the Cultural-Historical Theory (THC) and Children's Literature in the process of development of human capacities, especially of children in Early Childhood Education. The THC assures that the development of human capacities begins at an early age through the appropriation of elements of culture, propitiated in social relations. Children's Literature, which belongs to the universe of culture, may contribute to in this process and in the integral formation of children, as emphasized by authors and in and in the guiding documents of Brazilian Early Childhood Education researched. These considerations are, therefore, the result of a qualitative, bibliographic, and documental research. We conclude that improved teacher training is essential to provide literary experiences in kindergartens and preschools that are able to enhance the human development of children. human development of children.